Optimal solution for the index coding problem using network coding over GF(2) - Qureshi, Jalaluddin (2013)
The index coding problem is a fundamental transmission problem which occurs in a wide range of multicast networks. Network coding over a large finite field size has been shown to be a theoretically efficient solution to the index coding problem. However the high computational complexity of packet encoding and decoding over a large finite field size, and its subsequent penalty on encoding and decoding throughput and higher energy cost makes it unsuitable for practical implementation in processor and energy constraint devices like mobile phones and wireless sensors. While network coding over GF(2) can alleviate these concerns, it comes at a tradeoff cost of degrading throughput performance. To address this tradeoff, we propose a throughput optimal triangular network coding scheme over GF(2). We show that such a coding scheme can supply unlimited number of innovative packets and the decoding involves the simple back substitution. Such a coding scheme provides an efficient solution to the index coding problem and its lower computation and energy cost makes it suitable for practical implementation on devices with limited processing and energy capacity.